Penerapan Lean Software Development Method Dalam Merancang E-Scm Bahan Baku Banana Chips - Sa'adah, Nur; Kurniawan, Edi; M, Yori Apridonal (J-Com (Journal of Computer), 2025)
Abstract: In an increasingly competitive business era, information technology is key to managing data and information. E-SCM emerges as a strategic solution to integrate partners and manage inventory efficiently. This study focuses on the application of the Lean Software Development method to design an E-SCM system in the Banana Chips industry, which faces challenges in managing inventory and production processes. The main problems faced include the inability to manage raw material inventory and non-computerized records, resulting in inefficient use of time and costs. By applying Lean principles, such as eliminating unnecessary features, fast delivery, and team collaboration, the E-SCM Website is designed to be responsive to market needs and easy to understand by users. Before the E-SCM system is applied by users, developers test the system by measuring how well the system is understood by users. Before being implemented, the system was tested using the Usability Scale System (SUS) and prototype testing. The results of the questionnaire filled out by 5 respondents showed an average SUS score of 78, which was categorized as "Acceptable" and "Good". Keywords: lean software development method; e-scm; banana chips; inventory management; usability testing Abstrak: Dalam era bisnis yang semakin kompetitif, teknologi informasi menjadi kunci dalam pengelolaan data dan informasi. E-SCM muncul sebagai solusi strategis untuk mengintegrasikan mitra kerja dan mengelola stok barang secara efisien. Penelitian ini fokus pada penerapan metode Lean Software Development untuk merancang sistem E-SCM di industri Banana Chips, yang menghadapi tantangan dalam pengelolaan persediaan dan proses produksi. Masalah utama yang dihadapi mencakup ketidakmampuan dalam mengatur persediaan bahan baku dan pencatatan yang belum terkomputerisasi, mengakibatkan inefisiensi penggunaan waktu dan biaya. Dengan menerapkan prinsip-prinsip Lean, seperti menghilangkan fitur-fitur yang tidak perlu, pengiriman cepat, dan kolaborasi tim, Website E-SCM dirancang agar responsif terhadap kebutuhan pasar dan mudah dipahami oleh pengguna. Sebelum sistem E-SCM diaplikasikan oleh pengguna, pengembang melakukan pengujian terhadap sistem tersebut dengan mengukur seberapa baik sistem dimengeri oleh pengguna. Sebelum diterapkan, sistem diuji menggunakan Sistem Usability Scale (SUS) dan pengujian prototype. Hasil dari kuesioner yang diisi oleh 5 responden menunjukkan skor rata-rata SUS sebesar 78, yang dikategorikan sebagai “Acceptable” dan “Good”. Kata kunci: metode lean software development; e-scm; banana chips; pengelolaan persediaan; usability testing